Analisa Aplikasi Hedging Sebagai Perlindungan Transaksi Ekspor Oleh Eksportir Di Sulawesi Selatan - Usman Adami (JURNAL MANAJEMEN MOTIVASI, 2014)
This study aimed to examine the effect of exchange rate value of the forward rate hedging transactions carried out by the exporter. Transaction data used are five export commodities of 6 exporter in Southern Sulawesi with the number of transactions was 612 times. To calculate the multiple regression equation used method OLS (Ordinary Least Square). Results are transasksi value hedging is done by 6 to 5 export commodity exporters in South Sulawesi was very influenced significantly by Value Forward Spot Rate (X), with regard to indicators of external factors before deciding to make Hedging Export.